2020
DOI: 10.1128/msphere.00754-20
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Genomic Terminals of SARS-CoV-2 as Coevolving Functional Elements and Potential Therapeutic Targets

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has infected over 40 million people worldwide, with over 1 million deaths as of October 2020 and with multiple efforts in the development and testing of antiviral drugs and vaccines under way. In order to gain insights into SARS-CoV-2 evolution and drug targets, we investigated how and to what extent the SARS-CoV-2 genome sequence differs from those of other well-characterized human and animal coronavirus genomes, as well as how polymorphic SARS-CoV-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 61 publications
4
46
0
7
Order By: Relevance
“…The time series of the type C obtained by autoencoder analysis seems to be consistent with the emergence and disappearance and geo location of coevolving variant group 4 (CEVg4) reported by Chan et al (Chan et al 2020). Based on genome frequencies and geo locations, our classification of types A1, A2, B1, and D seemed to correspond to the wild type, CEVg3, CEVg1, and CEVg6, respectively.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The time series of the type C obtained by autoencoder analysis seems to be consistent with the emergence and disappearance and geo location of coevolving variant group 4 (CEVg4) reported by Chan et al (Chan et al 2020). Based on genome frequencies and geo locations, our classification of types A1, A2, B1, and D seemed to correspond to the wild type, CEVg3, CEVg1, and CEVg6, respectively.…”
Section: Resultssupporting
confidence: 89%
“…We found the eight clusters using over 30,000 SARS-CoV-2 ORF1ab genes in the NCBI Virus database, whereas Chan et al identified nine CEVg using 86,450 genomes in the GISAID database (Chan et al 2020). Yet there is not enough data to rigorously compare the differences between the ABCDE and CEVg classifications.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, increased expression of miR-1307-3p leads to a reduction in SARS-CoV-2 replication [ 5 ]. Also, Chen et al reported that mutations in SARS-CoV-2 3′-UTR lead to virus escape from the host immune system [ 16 ]. On the other hand, miR-1307-3p can affect anti-apoptotic proteins like BCL2 to induce apoptosis and inhibit proliferation.…”
Section: Mirnas Against Covid-19mentioning
confidence: 99%
“…To answer the latter, a database of all SNPs in the GISAID global collection 16 was generated and periodically updated by downloading all the genomes and filtering them for quality and completeness, then aligning to the WuHan-Hu-1 reference to identify any variants, as described 30 . The list of all variants and metadata for each sample were then put into a relational database for fast querying.…”
Section: Phylogenetic Inferencementioning
confidence: 99%